Lessons from a survey of China's economic diplomacy - Simplice Asongu; Jacinta C. Nwachukwu; Gilbert A. A. Aminkeng (African Governance and Development Institute (AGDI), 2018)
Today, the West faces a considerable dilemma in their support for the Washington Consensus as a dominant approach for development because the Beijing model has grown to become an unavoidable process which can only be neglected at the cost of standing on the wrong side of economic history. The Washington Consensus, the hitherto dominant scheme, is being encroached on by the Beijing model. Many African nations are increasingly embracing this later method because the prevailing Western model has failed to deliver on a number of objectives. This is increasingly evident because China's economic diplomacy has been politely and strategically coined to achieve it. A case study is used herein to articulate the different strands of the survey. The paper puts some structure on China's economic diplomatic strategies and discusses lessons for Africa, China and the West. It contributes to existing literature by critically assessing why it is necessary for the West to modify the conception and definition of the Washington Consensus as a counterpart to the Beijing model. In order to remain relevant in the 21st century and beyond, the Washington Consensus should incorporate those ideas which are in conformity with Moyo's (2013) conjecture. This postulates that, while the Beijing model is optimal in the short-run, the Washington Consensus remains the ideal long-term development model because it is more inclusive of the rights demanded by individuals at different income categories.
Keywords: F19; F21; O10; O19; O55; 330; Economic relations; China; Africa